Key information sources influencing prospective students’ university choice – a South African perspective - Lubbe, Isolde; Petzer, Daniel (South African Journal of Higher Education, 2016)
Universities are facing increasingly complex trends and challenges in attracting and retaining the best students. This has coaxed university marketers to embrace marketing practices and ideas in order to acquire and retain these students. The study aims at understanding potential students’ decision-making with respect to what and who influences them when choosing a university. The research design is descriptive and self-administered questionnaires were fielded to first-year students at a comprehensive university early in the academic year. A total of 1 290 useable responses were realised. The study uncovered that brochures and the students’ parents are most influential in their choice. Significant differences were uncovered based upon demographics of respondents and key information sources that influence university choice. The findings imply that university marketers should segment the prospective student market by taking into account that prospective students differ with regard to the extent of who and what influence their university choice. Key words: South African Higher Education, South African university, prospective student, university choice, key information sources, decision-making process.